System for reproducible code environments - Dohrnii - Mileski, Dimitar; Gushev, Marjan (My University, 2022)
The reproducibility of code and the whole environment in which that code needs to be executed takes up much of the time of software engineers, computer scientists, and anyone who writes code. There are several reasons why we can not get the same results if the original data is available to us. This may be because the environment is not configured the same way as the source code author, we do not have enough knowledge of the technology used, poorly written documentation, lack of documentation, different versions of libraries, tools, development frameworks, mistakes made by one who wants to reproduce the code or there are errors in the code or errors that occurred after a certain period of time. In this paper, we introduce a new system for reproducible coding environments called Dohrnii, as a cloud-based solution. The main purpose is to save the time lost when we want to reproduce the results of a project for the first time. Every Dohrnii environment contains a video, description, instance (virtual machine), resources, and evaluation. This means that with this system it will be possible to reproduce environments in which the code needs to be executed, for that there will be a video where it will be shown how to reproduce the code, instance (virtual machine), description, additional resources, and part for an evaluation to determine if what is in the video corresponds to what is in the instance.
Keywords: code reproducibility, code environment, web platform, cloud computing